Large-scale disasters and the insurance industry - Krämer, Walter; Schich, Sebastian (Assurances et gestion des risques / Insurance and Risk Management, 2008)
The authors investigated the impact of the 20 largest – in terms of insured losses – man-made or natural disasters on various insurance industry stock indices. They show via an event study that insurance sectors worldwide are quite resilient, in a market–value sense, to unexpected losses to capital. The data provide evidence that equity market investors believe that insurance companies will on average be able to make losses back over the foreseeable future, i.e. that the adverse shocks to equity which have resulted from these catastrophes will be compensated by either an outward shift of the demand curve or by an ability to raise premiums, or both.